MEMBANGUN SERVER LEARNING MANAGEMENT SYSTEM SEBAGAI MEDIA PEMBELAJARAN PADA KURSUS KOMPUTER LPK SULTHOON 4M DENGAN UBUNTU SERVER - Martoni Martoni; Toibah Umi Kalsum; Hendri Alamsyah (UNIVED Press, 2024)
Utilizing the use of the Learning Management System can help the Skills Institute at LPK Sulthoon 4M in facilitating online learning. The learning management system implemented on a virtual private server (VPS) aims to use a more economical server. The research method used is the Waterfall Prototype method which involves gathering requirements, building a prototype, evaluating the system, testing the system, evaluating the system and using the system. The Learning Management System runs on Moodle software which is used by admins, course instructors and students. This Moodle software accelerates and facilitates students learning online without time limits. From the research results, this system makes it easier for students to study courses at training institutions and courses by applying information technology.